Geomorphological patterns and sedimentary facies in a modern mixed carbonate-siliciclastic lagoon (New Caledonia) - Elsa Tournadour; Axel Ehrhold; Pascal Le Roy; Samuel Etienne; Stephan J. Jorry; Gwenael Jouet; Julien Collot; Martin Patriat; Charline Guérin; Guillaume Michel; Camille Decultot; Etienne Tertrais; et al. (Journal of Maps)
The New Caledonian lagoon is of particular interest for studying the controls on mixed carbonate–siliciclastic sedimentation. The large southwestern lagoon is bordered by a massive barrier reef only interrupted by few passes, while the narrower and shallower eastern lagoon is characterized by a more discontinuous barrier reef that is partially submerged to the South. Using bathymetric, backscatter imagery and seabed sampling, this study presents a sedimentary mapping at a 1/70,000 scale for four zones, using a harmonized facies classification and presented on a single panel (Main Map). This high-resolution mapping highlights the surface sediment distribution, the diversity of bioconstructed morphologies and the architecture of drainage networks. Our map suggests that the southwestern lagoon is more prone to fine-grained sedimentation than the southeastern lagoon. The latter shows meandering channels, in places parallel to the shore. These differences are likely due to inherited morphologies and to contrasted hydrodynamic conditions between both margins.